2022
DOI: 10.34118/jbms.v9i1.1895
|View full text |Cite
|
Sign up to set email alerts
|

Free vibrational analysis of composite beams reinforced with randomly aligned and oriented carbon nanotubes, resting on an elastic foundation

Abstract: The main interest of this paperwork is to examinate the dynamic behavior (free vibrational response) of carbon nanotubes (CNT) composite beams standing on an elastic foundation of Winkler-Pasternak’s. The affected beam consists of a polymer matrix reinforced with single-wall carbon nanotubes (SWCNT’s), in which, a large number of CNT’s reinforcement of infinite length are distributed in a linear elastic polymer matrix. In this study the CNT’s are considered either aligned or randomly oriented on the matrix.&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…By substituting Equation (20) into Equation ( 24), one obtains the stress resultants in form of material stiffness and displacement components:…”
Section: Principle Of Virtual Workmentioning
confidence: 99%
See 1 more Smart Citation
“…By substituting Equation (20) into Equation ( 24), one obtains the stress resultants in form of material stiffness and displacement components:…”
Section: Principle Of Virtual Workmentioning
confidence: 99%
“…Harrat et al [19] conducted an analytical study of concrete beams incorporated with nano-silica particles using the Voigt model to describe the agglomeration effect of silica nanoparticles in the matrix and then studied the static behavior of nano-SiO 2 reinforced concrete beams resting on the Winkler-Pasternak foundation. When Chatbi et al [20] also investigated the bending behavior of SiO 2 -reinforced concrete slabs resting on Kerr's elastic foundation, the most findings of those studies indicate that the use of an optimum amount of SiO 2 nanoparticles on concretes increases better mechanical behavior. In addition, they concluded that the elastic foundation has a significant impact on the bending of concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies concluded that the addition of these entities enhances the mechanical properties of concrete while concurrently affecting its thermal characteristics due to the nanoparticles' high thermal conductivity. In a separate study, Chatbi et al [22] conducted a mechanical analysis of polymer structures reinforced with either aligned or randomly aligned carbon nanotubes using the MORI-TANAKA approach. The findings highlighted a significant enhancement in the mechanical properties of polymers due to carbon nanotubes reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Harrat et al [ 19 ] presented a comprehensive study on the static behavior of nano-SiO 2 -based concrete beams resting on an elastic foundation. Similarly, Chatbi et al [ 20 ] investigated the bending analysis of nano-SiO 2 -reinforced concrete slabs supported by an elastic foundation. These studies collectively established that the incorporation of SiO 2 nanoparticles in concrete yields increased their mechanical resistance, reduced the deflections, diminished the stresses, and lowered the vibrational natural frequencies.…”
Section: Introductionmentioning
confidence: 99%